SOCIOLOGICAL PORTRAIT OF THE SENIOR OF THE UNIVERSITY (ELITE) GYMNASIUM IN TYUMEN REGION - Gennady F. Shafranov-Kutsev; Galina Z. Efimova (Образование и наука)
The aim of the study is to show and analyze the situation and aspects of work with gifted children and teenagers that are aimed at preservation of a gene pool of the country; and revealed to be the most important condition of formation of the future highly professional elite in Russia. The most efficient forms of establishing such activities are emphasized; the basic psychological and pedagogical methods of this activity are shown. The most important qualities of schoolaged children that are notable for not ordinary mental abilities are noted in the present study. Methods and techniques. The article presents the results of the empirical sociological survey of senior schoolchildren and the results of the sample survey of senior students undertaken in five regions of the Ural Federal District. The software package for statistical analysis (SPSS) was used for data evaluation. Scientific novelty. Federal and regional infrastructure oriented to work with gifted children is considered in the study; the ways of efficiency assessment are investigated. The concept «elite school (high-class)» is refined. The sociological portrait of the senior pupil trained in specially created establishment of the elite general education is presented. Results. The authors pay special attention to the analysis of the focused work with gifted children and teenagers in the Tyumen region. A special focus is laid on the Academic Gymnasium of Tyumen State University that was included in the list of top 25 secondary schools of Russia. Spiritually-moral values and social-professional choices of senior students both of an elite gymnasium and ordinary secondary schools are revealed and compared in the course of sociological research. It is found out that gymnasium schoolchildren are remarkable for their social optimistic approach to their life, they are more pragmatic in the issues of their future professional preferences, and moreover, they are active in their choices and career guidance. But there are also some negative issues that have to be adjusted within educational work. It is important to achieve as more as possible adequate, realistic student’ self-estimation of their potential and possibilities; to take steps for number decrease «potential migrants» among the most talented part of youth. Practical significance. The research results can be used while deepening the scope of knowledge on the sociological graduates’ portrait of elite or high-class educational institutions. These results can also lay the basis for undertaking some steps that would make the native city and the region more attractive for talented youth. The research methodology can be used by scholars in the field of sociology, psychology and pedagogics for pre-arranged and strategic researches implementation.